2010
DOI: 10.1186/1472-6874-10-22
|View full text |Cite
|
Sign up to set email alerts
|

The LIFESTYLE study: costs and effects of a structured lifestyle program in overweight and obese subfertile women to reduce the need for fertility treatment and improve reproductive outcome. A randomised controlled trial

Abstract: BackgroundIn the Netherlands, 30% of subfertile women are overweight or obese, and at present there is no agreement on fertility care for them. Data from observational and small intervention studies suggest that reduction of weight will increase the chances of conception, decrease pregnancy complications and improve perinatal outcome, but this has not been confirmed in randomised controlled trials. This study will assess the cost and effects of a six-months structured lifestyle program aiming at weight reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 45 publications
0
65
0
3
Order By: Relevance
“…Interventions to combat prepregnancy obesity with lifestyle modifications are only recently coming to the foreground of investigative attention (22,23). Most published studies on this subject lack sufficient length of follow-up and only involved women (24).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to combat prepregnancy obesity with lifestyle modifications are only recently coming to the foreground of investigative attention (22,23). Most published studies on this subject lack sufficient length of follow-up and only involved women (24).…”
Section: Discussionmentioning
confidence: 99%
“…From studies with interventions initiated before pregnancy (e.g., the Radiel study [67] or LIFESTYLE study [68]), no data are available on percentage body fat or fetal insulin levels at present. Hopefully, these data will become available in the coming years.…”
Section: How To Prevent the Fetal Changes In Maternal Diabesitymentioning
confidence: 99%
“…Six of the studies investigated reproductive function after treatment with medical therapies including metformin, orlistat, sibutramine, and myoinositol [58][59][60][61][62][63] . One study outlined the strategy of an ongoing trial evaluating the costs and effects of a structured lifestyle program in overweight and obese subfertile women in Norway, but no results were available 64 . Only one study reported specifically on the effects of a lifestyle intervention on reproductive function in obese women, and this was in obese women preparing to undergo IVF 65 .…”
Section: Weight Loss Through Lifestyle Changesmentioning
confidence: 99%